At the Intersection of Ecofeminism and Religion: Directions for Consideration - Eaton, Heather (Journal for the study of religion, nature and culture, 2001)
Ecological feminism has developed from many directions and locations, and with differentiated links between feminism and ecology and between women and nature. Religious discourses are taking ecofeminist analyses into their folds. As a whole, however, religious ecofeminist perspectives are uneven. In this article, I suggest seven hermeneutics that might strengthen religious ecofeminist discourses as well as develop connections among the various viewpoints towards larger horizons, and specifically ones that link theory with concrete and material life-conditions.